2008
DOI: 10.1128/iai.00112-08
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Role of Macrophages and Neutrophils in Host Antiprotozoan Resistance in Mice Acutely Infected withCryptosporidium parvum

Abstract: Severe experimental infections with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…Macrophages have been shown to produce large amounts of IFN-␥ in vitro when stimulated with a combination of IL-12 and IL-18 (22), both of which are expressed during cryptosporidial infection (16,26). In relation to our findings, other workers recently reported that the transference of peritoneal macrophages from C. parvum-infected mice to immunocompromised mice with a macrophage deficiency allowed the recipients to be resistant to infection with the parasite, and in vitro studies suggested that IFN-␥ from neutrophils might be involved in activation of the macrophages (25). DCs might also have an important protective role in this respect, as they have been found to be a potent source of IFN-␥ when activated by cytokines (11).…”
Section: Discussionsupporting
confidence: 84%
“…Macrophages have been shown to produce large amounts of IFN-␥ in vitro when stimulated with a combination of IL-12 and IL-18 (22), both of which are expressed during cryptosporidial infection (16,26). In relation to our findings, other workers recently reported that the transference of peritoneal macrophages from C. parvum-infected mice to immunocompromised mice with a macrophage deficiency allowed the recipients to be resistant to infection with the parasite, and in vitro studies suggested that IFN-␥ from neutrophils might be involved in activation of the macrophages (25). DCs might also have an important protective role in this respect, as they have been found to be a potent source of IFN-␥ when activated by cytokines (11).…”
Section: Discussionsupporting
confidence: 84%
“…Although NET formation was initially characterized in response to bacteria and protozoa [20, 27], it has also been reported for larger multi-cellular pathogens including fungi and three species of parasitic nematodes [19, 24, 25]. Our initial experiments co-culturing B .…”
Section: Resultsmentioning
confidence: 99%
“…stercoralis L3 [23]. In several studies PMNs have been shown to co-operate with monocytes or macrophages in immunity against parasites, including helminths [18, 2427]. …”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils have been shown to play an active role in the control of infections with specific and distinct pathogens such as Legionella (17), Toxoplasma (27), Mycobacterium (28), Entamoeba (29), Histoplasma (30), and Cryptosporidium (31). BALB/c mice infected in the ear dermis with L. braziliensis develop cutaneous lesions at the site of inoculation and histological analyses of infected ear sections have demonstrated a constant recruitment of neutrophils to the inoculation site (14).…”
Section: Discussionmentioning
confidence: 99%